Long‐term functional airway assessment after open airway surgery for laryngotracheal stenosis. (24th June 2015) - Pullens, Bas; Pijnenburg, Marielle W.; Hoeve, Hans J.; Baatenburg de Jong, Rob J.; Buysse, Corinne M. P.; Timmerman, Marieke K.; van der Schroeff, Marc P.; Joosten, Koen F. M.
Abstract : Objectives/Hypothesis: The purpose of this study was to evaluate our patient‐reported and objective long‐term outcomes of patients treated for laryngotracheal stenosis. Study Design: Prospective cohort study. Methods: Sixty‐five patients were evaluated after a median follow‐up of 7 years after surgery. Follow‐up measurements consisted of pulmonary function testing, Bruce treadmill test, and Child Health Questionnaires (CHQ). Results: Pulmonary function tests were available in 43 patients, and 30/43 had abnormal forced expiratory volume in 1 second/forced inspiratory volume in 1 second (FIV1), 25/43 had abnormal FIV1/maximum vital capacity, and 24/43 had abnormal peak expiratory flow. One‐third of patients had reduced exercise tolerance. CHQ revealed significant positive correlations with pulmonary function results and exercise tolerance. Multivariate analysis showed that glottic involvement of the stenosis and the presence of comorbidities at time of surgery are the only factors for poor long‐term functional outcome. Conclusions: The majority of patients show deficits in pulmonary function and exercise tolerance related to lower scores of quality of life. Glottic involvement of the stenosis and the presence of comorbidities are the only significant factors for poor functional outcome. Long‐term multidisciplinary follow up is mandatory after surgery for laryngotracheal stenosis. Level of Evidence: 2B. Laryngoscope, 126:472–477, 2016